Tactful Networking as a cornerstone for opportunistic human-aware D2D communication - Costa, Rafael L.; Sampaio, Leobino N.; Viana, Aline C. (Companion Proceedings of the Brazilian Symposium on Computer Networks and Distributed Systems (SBRC); 2022: Companion Proceedings of the 40th Brazilian Symposium on Computer Networks and Distributed Systems, 2022)
In this thesis, we guided the reader through the whole process for building a novel Tactful Opportunistic COmmunicaTion Strategy (TOOTS). TOOTS leverages wireless encounter patterns, temporal, spatial, geographic, and direction awareness to improve cost-effectiveness content delivery in a mobile networks scenario. The proposal consists of: learning human-aspect stateof-art best practices; achieving insights to improve strategy’s performance; using, proposing, and analyzing human-aware metrics; combining metrics and insights into the strategy targeting an improved performance in a more realistic mobile scenario; and finally, evaluating the strategy through its strengths and shortcomings. This thesis shows that TOOTS improved the performance of an opportunistic content delivery scenario in terms of overhead, delivery rate, and latency by following this process. The strategy can be applied in different scenarios to assist the operator in delivering content without not necessarily using their legacy network, e.g., by exploring the capillarity of their mobile users, for data offloading and other applications.